A problem-based learning health literacy intervention program on improving health-promoting behaviors among girl students - Neda Karimi; Shahrzad Saadat-Gharin; Azar Tol; Roya Sadeghi; Mehdi Yaseri; Bahram Mohebbi (Wolters Kluwer Medknow Publications, 2019)
BACKGROUND: Health-promoting behaviors are essential beliefs and actions to develop and sustain the adolescent health; however, people with inadequate health literacy have poorer health status. This study aimed to determine the effect of a problem-based learning (PBL) health literacy program on improving health-promoting behaviors among female students (15-18 years) at high schools in 2018-2019. METHODS: This study was a quasi-experimental intervention one which carried out on 377 girl students using a cluster sampling method of intervention (n = 183) and control (n = 194) groups. The intervention was performed in four educational sessions of PBL health literacy program using related scenarios for 90 min. Data were collected through demographic variables, the Health Literacy Measure for Adolescents, and the Health-Promoting Lifestyle Profile II. Participants filled the questionnaires immediately and 3 months after the intervention in both the groups. RESULTS: There were significant differences comparing the mean score of health literacy dimensions in numeracy (P < 0.001), use (P < 0.001), communication (P < 0.001), access (P = 0.03), self-efficacy (P < 0.001), and total health literacy (P < 0.001) after intervention. These differences also observed in numeracy (P < 0.001), use (P = 0.03) and total health literacy (P < 0.001) in follow-up between the intervention and control groups. The mean scores of health-promoting lifestyle dimensions in all dimensions immediately after intervention (P < 0.001) and follow-up (P ≤ 0.006) showed significant differences between the two groups, while the intervention group revealed a higher mean scores. CONCLUSION: It seems that PBL health literacy and practicing real-life scenarios can improve the adolescent lifestyle. It is recommended to examine the effectiveness of the program for other health-related behaviors among other populations.